2011
DOI: 10.2174/092986711795843218
|View full text |Cite
|
Sign up to set email alerts
|

STAT-3 Inhibitors: State of the Art and New Horizons for Cancer Treatment

Abstract: The signal transducers and activators of transcription (STATs) include a class of cytoplasmic signaling proteins whose role in the regulation of cell growth and survival is mediated by phosphorylation of a critical tyrosine residue within the STAT protein. This occurs in response to cytokines and growth factors modulating the expression of specific target genes. In particular, phosphorylation induces STAT:STAT dimer formation between two monomers, via reciprocal phosphoTyr (pTyr)-SH2 domain interactions. To da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 105 publications
0
52
0
Order By: Relevance
“…To our knowledge, this is the first report that provides evidence suggesting that STAT1 and STAT3 appear to regulate CXCL10 level during sterile inflammation. Our data suggest that STAT1 and STAT3 inhibitors, which are being developed to treat cancers and inflammatory diseases, 76,77 may be potentially suitable to block CXCL10-mediated retinal inflammation and save retinal neurons in TON.…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, this is the first report that provides evidence suggesting that STAT1 and STAT3 appear to regulate CXCL10 level during sterile inflammation. Our data suggest that STAT1 and STAT3 inhibitors, which are being developed to treat cancers and inflammatory diseases, 76,77 may be potentially suitable to block CXCL10-mediated retinal inflammation and save retinal neurons in TON.…”
Section: Discussionmentioning
confidence: 85%
“…22 IL-17A had recently been reported to stimulate Stat3 activation through a positive feedback loop in inflammatory cells, fibroblasts, as well as the growth of B16 melanoma and MB49 bladder carcinoma. 27 As Stat3 activation in tumor cells and tumor-associated inflammatory cells played a critical role in tumor progression by augmenting tumor survival and tumor angiogenesis, and suppressing antitumor immunity, [24][25][26] we therefore detected the Stat3 activity in OS cells in response to IL-17A/IL-17RA interaction. Indeed, here we found that IL-17A/IL-17RA interaction could effectively induce the Stat3 activation in OS cells.…”
Section: Discussionmentioning
confidence: 98%
“…It is well acknowledged that Stat3 activation in tumor cells and tumor-associated inflammatory cells played a critical role in tumor progression by augmenting tumor survival and tumor angiogenesis, and suppressing antitumor immunity. [24][25][26] Recent study showed that IL-17A could stimulate Stat3 activation in B16 melanoma and MB49 bladder carcinoma cells. 27 We therefore determined whether the IL-17A/IL-17RA interaction could promote the Stat3 activity in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the central role of aberrant STAT3 signalling in ovarian cancer pathogenesis, this compound may provide a useful starting point for the development of chemical scaffolds to block STAT3 signalling for cancer therapy (Madoux et al, 2010). In particular, STAT3 dimerization inhibitors could play a significant role in the future of cancer and adjuvant cancer therapies (Lavecchia et al, 2011). STAT3 activation is also induced by hypoxia that is commonly observed in many solid tumours and represents a major obstacle to chemo-or radiation therapy.…”
Section: Inflammation and Possible Therapeutic Implicationsmentioning
confidence: 99%